COVID‐19 vaccination not associated with increased risk of erectile dysfunction. (8th September 2022) - Diaz, Parris; Zizzo, John; Blachman‐Braun, Ruben; Gandhi, Deep Asit; Reddy, Rohit; Zucker, Isaac Jake; Dullea, Alexandra; Khodamoradi, Kajal; Ramasamy, Ranjith
Abstract: Although mRNA COVID‐19 vaccines have proven to be safe and effective against SARS‐CoV‐2, vaccination rates have slowed, with some individuals citing impotence as a concern. Therefore, we conducted a survey of the US males to evaluate the impact of COVID‐19 vaccination on erectile function. We hypothesized that vaccinated men would not have a higher risk of ED compared to unvaccinated men. Amazon Mechanical Turk (MTurk) was utilized to survey the US adult male population between August 26 and September 2, 2021. Survey participation was open to 1000 males over the age of 18 and currently living in the United States regardless of vaccination status or the past medical history of COVID‐19. Selection criteria included respondents ≥45 years old, no history of physician‐diagnosed ED, biologically born, and identify as male. Participants completed an anonymous 16‐question survey that included a multidimensional scale used to evaluate ED, the International Index of Erectile Function (IIEF‐5). Among vaccinated men, the median IIEF‐5 score was 20 [16–24] compared to 22 [17.5–25] in the unvaccinated group ( p  = 0.195). The multivariable‐adjusted analysis demonstrated that vaccination against COVID‐19 was not associated with increased risk of ED. Overall, this cross‐sectional survey showed that COVID‐19 vaccination was not associated with an increased risk of erectile dysfunction in males 45 years and older.